Prospective risk of stillbirth and neonatal complications in twin pregnancies: systematic review and meta-analysis. (6th September 2016) - Cheong-See, Fiona; Schuit, Ewoud; Arroyo-Manzano, David; Khalil, Asma; Barrett, Jon; Joseph, K S; Asztalos, Elizabeth; Hack, Karien; Lewi, Liesbeth; Lim, Arianne; Liem, Sophie; Norman, Jane E; et al.
Abstract : Objective To determine the risks of stillbirth and neonatal complications by gestational age in uncomplicated monochorionic and dichorionic twin pregnancies. Design Systematic review and meta-analysis. Data sources Medline, Embase, and Cochrane databases (until December 2015). Review methods Databases were searched without language restrictions for studies of women with uncomplicated twin pregnancies that reported rates of stillbirth and neonatal outcomes at various gestational ages. Pregnancies with unclear chorionicity, monoamnionicity, and twin to twin transfusion syndrome were excluded. Meta-analyses of observational studies and cohorts nested within randomised studies were undertaken. Prospective risk of stillbirth was computed for each study at a given week of gestation and compared with the risk of neonatal death among deliveries in the same week. Gestational age specific differences in risk were estimated for stillbirths and neonatal deaths in monochorionic and dichorionic twin pregnancies after 34 weeks' gestation. Results 32 studies (29 685 dichorionic, 5486 monochorionic pregnancies) were included. In dichorionic twin pregnancies beyond 34 weeks (15 studies, 17 830 pregnancies), the prospective weekly risk of stillbirths from expectant management and the risk of neonatal death from delivery were balanced at 37 weeks' gestation (risk difference 1.2/1000, 95% confidence interval −1.3 to 3.6; I 2 =0%). Delay in delivery by a week (to 38 weeks) led to an additional 8.8 perinatal deaths per 1000 pregnancies (95% confidence interval 3.6 to 14.0/1000; I 2 =0%) compared with the previous week. In monochorionic pregnancies beyond 34 weeks (13 studies, 2149 pregnancies), there was a trend towards an increase in stillbirths compared with neonatal deaths after 36 weeks, with an additional 2.5 per 1000 perinatal deaths, which was not significant (−12.4 to 17.4/1000; I 2 =0%). The rates of neonatal morbidity showed a consistent reduction with increasing gestational age in monochorionic and dichorionic pregnancies, and admission to the neonatal intensive care unit was the commonest neonatal complication. The actual risk of stillbirth near term might be higher than reported estimates because of the policy of planned delivery in twin pregnancies. Conclusions To minimise perinatal deaths, in uncomplicated dichorionic twin pregnancies delivery should be considered at 37 weeks' gestation; in monochorionic pregnancies delivery should be considered at 36 weeks. Systematic review registration PROSPERO CRD42014007538.